Vote Trading in Power-Sharing Systems: A Laboratory Investigation. Issue 636 (20th August 2020) - Tsakas, Nikolas; Xefteris, Dimitrios; Ziros, Nicholas
Abstract: Vote trading in power-sharing systems—i.e., systems in which a voter's utility with respect to the election's outcome is proportional to the vote share of her favourite party—is, in theory, welfare improving. However, trading votes for money in majoritarian systems may have detrimental welfare effects, especially when voters' preference intensities are similar (Casella et al ., 2012 ). We use a laboratory experiment to test the effect of vote trading in each of these popular electoral systems on voter welfare and find strong evidence in support of the above intuitions: vote trading in power-sharing systems boosts aggregate welfare across all considered specifications, but it is not welfare improving in majoritarian systems. Importantly, and contrary to theoretical predictions, a substantial share of subjects consistently loses from vote trading even in power-sharing systems, indicating that its welfare effects are not unambiguous.